APPLICATION REALISTIC MATHEMATICS EDUCATION (RME) TO INCREASED THE MATHEMATICS LEARNING OUTCOMES OF ELEMENTARY SCHOOL SD NEGERI SALATIGA 12 - Ayuk Rismaya Putri; Irul Irul (JPSD (Jurnal Pendidikan Sekolah Dasar), 2019)
Abstract. This research was conducted to improve the learning result from SD Negeri Salatiga 12 on the 2nd  grade’s mathematics by applying Realistic Mathematic Education (RME) approach. The research was based on the Pre-test results by 73.7% of the students that do not fulfill the Minimum Criteria of Mastery Learning (KKM) which is 70. The completeness of students’ learning outcomes at pre-test stage reaches a percentage of 26.3%. This research is an Action Class Research (PTK) using pre-test and post-test. The subjects of this research are 38 of 2nd grade elementary students of SD Negeri Salatiga 12. The data obtained were analyzed using descriptive statistics and hypothesis which are tested by T-test (comparisons). The results showed that there is a significant differences between the pre-test and post-test which are taught with a Realistic Mathematics Education (RME) approach, which is the Sig (2-tailed) = 0.000 < 0.05 then Ho denied. From this results of research, shows the increased learning can be seen from the results of the Post-test that reach the presentage of mastery learning 84.2%. This can be stated that the Realistic Mathematics Education (RME) approach are able to improve the achievement of learning math of 2nd grade elementary students in SD Negeri Salatiga 12.  Keyword: Realistic Mathematics Education (RME), learning outcomes